Robustness of Improving Active Maglev Motorized Spindle Equilibrium Position - Zhang Yanhong; Zhao Dean; Zhang Jiansheng; Zheng Zhongqiao; Zou Yiqin; Zhang Yongchun (Institute of Advanced Engineering and Science, 2013)
The equilibrium position of active maglev motorized spindle had great influence on the industrial processing accuracy, in order to improve the performance of active maglev motorized spindle and processing accuracy, a new control method and control device of active maglev was put forward based on H∞ mixed sensitivity. Firstly, a mathematical model was established among the electromagnetic force on the rotor, control current and position displacement of the rotor center. Secondly, the H∞ mixed sensitivity control method was used, the selection method of weighting function was discussed and H∞robust controller was designed, the experimental results showed that for active maglev motorized spindle, the designed controller had better static and dynamic performance, position precision, so that the robustness of the motorized spindle equilibrium position was further improved, which met the requirement of high precision industrial process. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3263